Nonlinear analysis of stability for imperfect eccentrically stiffened FGM plates under mechanical and thermal loads based on FSDT. Part 1: Governing equations establishment - Dung, Dao Van; Nga, Nguyen Thi (Vietnam Journal of Mechanics, 2015)
In this paper, the buckling and post-buckling behaviors of eccentrically  stiffened functionally graded material (ES-FGM) plates on elastic  foundations subjected to in-plane compressive loads or thermal loads are  investigated by an analytical solution. The novelty of this work is that FGM  plates are reinforced by FGM stiffeners and the temperature, stiffener,  foundation are considered. The first-order shear deformation  plate theory is used. The thermal elements of plate and stiffeners in  fundamental equations are introduced. Theoretical formulations based on the  smeared stiffeners technique and the first-order shear deformation plate  theory, are derived. The analytical expressions to determine the static  critical buckling load and post-buckling load-deflection curves are  obtained.